2000
DOI: 10.1002/j.2048-7940.2000.tb01864.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Structured Education Course on Stroke Survivors Living in the Community

Abstract: Forty‐one community dwelling stroke survivors were measured on three dependent variables—depression, hope, and ways of coping—in this quasi‐experimental, repeated‐measure study. The subjects were randomly assigned to a treatment group or control group. The treatment group attended a series of eight 2‐hour educational classes during a 4‐week period. At the end of the series of classes, the tests of depression, hope, and ways of coping were readministered to the subjects in both groups. The results of comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
1
41
1
Order By: Relevance
“…A Cochrane review concluded that meeting the expressed informational needs of patients and carers should be the focus of future research [48]. The disparity between what health professionals think patients and their carers want to know and what patients and carers actually want to know has been highlighted by a number of authors [49][50][51]. The importance of establishing the informational needs of patients and carers and designing an education intervention to meet those needs cannot be underestimated.…”
Section: Discussionmentioning
confidence: 94%
“…A Cochrane review concluded that meeting the expressed informational needs of patients and carers should be the focus of future research [48]. The disparity between what health professionals think patients and their carers want to know and what patients and carers actually want to know has been highlighted by a number of authors [49][50][51]. The importance of establishing the informational needs of patients and carers and designing an education intervention to meet those needs cannot be underestimated.…”
Section: Discussionmentioning
confidence: 94%
“…21,28 This suggests that information sessions should be conducted, where possible, with both the client and carer together or in small groups, but one-on-one sessions with the health professional should be offered as appropriate for the content being discussed or to accommodate variation in clients' and carers' preferences. 29,30 Studies of educational interventions for people living in the community after stroke have evaluated the effectiveness of providing the information in participants' homes, 31,32 at community-based centres, [33][34][35][36] and over the telephone. 37 Even though there can be some restrictions to providing information via the telephone (such as limited use of nonverbal cues), clients with stroke and their carers have reported a desire to receive 29 and satisfaction with receiving 38 telephone support when it is a supplement to or follow-up component of face-to-face information provision.…”
Section: Format Of Information Provisionmentioning
confidence: 99%
“…Proper education and training may thus help caregivers provide appropriate care to survivors of stroke, and lessen the emotional and physical burden of the caregivers (Dale et al, 1997). It will also help the stroke survivors reintegrate into the community (Johnson and Pearson, 2000). As a stroke educational group is a means that is commonly used to deliver stroke-related knowledge, help caregivers with care-giving techniques, and individuals with stroke and their caregivers adjust to life (Barton et al, 2002), a further exploration of the effects of such a group, and of continuous improvements in stroke educational programs, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Neglect of the need of both patients and caregivers to acquire sufficient knowledge in adapting to the changes resulting from a stroke is not uncommon (Brereton and Nolan, 2000). It has been suggested that the educational group is an effective way to provide a channel for a more structured delivery of stroke knowledge (Johnson and Pearson, 2000;Warner, 2000), and to enhance sharing and provide psychological support among stroke survivors and caregivers (Rodgers et al, 1999). In addition, a stroke educational program can increase the knowledge base of both the stroke individuals and their caregivers so that they can recognize the early signs of stroke (Rausch and Turkoski, 1999;Rodgers et al, 1999;Stern et al, 1999;Barton et al, 2002), increase their success in reducing the incidence of recurrent strokes (Rausch and Turkoski, 1999) and reduce the anxiety of caregivers about their skills in caring for people with stroke (Hanger et al, 1998;Banford et al, 2001).…”
Section: Introductionmentioning
confidence: 99%